Basic psychological needs satisfaction, intrinsic motivation, and studying sports protect university student-athletes from burnout: insights from Latvia - Svens Vilks; Aleksandrs Kolesovs (Frontiers in Sports and Active Living)
The study explored the prediction of athlete burnout by basic psychological needs satisfaction in sports, combined with the intrinsic motivation in sports and sociodemographic characteristics of university student-athletes. The protective effects of both psychological predictors were expected. The participants were 219 university student-athletes aged 19–33 (M = 22.3 and SD = 3.2 years) who participated in sports from recreational (38%) up to World/Olympic (9%) levels, with a mean sports experience of 10.1 (SD = 5.2) years. The study used three surveys, presented in Latvian: Sports Motivation Scale-II, Basic Psychological Needs in Exercise Scale, and Athlete Burnout Questionnaire. Higher need satisfaction was the main predictor of lower burnout and a higher sense of accomplishment in the frame of SEM. Higher intrinsic motivation, participants' age, and studying sports also predicted lower burnout and competing at World/Olympic level predicted a higher sense of accomplishment. The bifactor model confirmed athlete burnout as a syndrome integrating its specific components. As the main protective factor, psychological needs satisfaction in sports should be prioritized in university student-athlete training.